2020
DOI: 10.7554/elife.57761
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide CRISPR screens of oral squamous cell carcinoma reveal fitness genes in the Hippo pathway

Abstract: New therapeutic targets for oral squamous cell carcinoma (OSCC) are urgently needed. We conducted genome-wide CRISPR-Cas9 screens in 21 OSCC cell lines, primarily derived from Asians, to identify genetic vulnerabilities that can be explored as therapeutic targets. We identify known and novel fitness genes and demonstrate that many previously identified OSCC-related cancer genes are non-essential and could have limited therapeutic value, while other fitness genes warrant further investigation for their potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 95 publications
(175 reference statements)
7
38
0
Order By: Relevance
“…Furthermore, it has to be analyzed whether there are differences in regard to Trop-2 expression between Asian and Caucasian OSCC. Several studies on the genomic landscape of Asian and Caucasian OSCC have already revealed distinct molecular differences, which are supposed to be partly due to varying population-specific risk factors (summarized in [ 35 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has to be analyzed whether there are differences in regard to Trop-2 expression between Asian and Caucasian OSCC. Several studies on the genomic landscape of Asian and Caucasian OSCC have already revealed distinct molecular differences, which are supposed to be partly due to varying population-specific risk factors (summarized in [ 35 ]).…”
Section: Discussionmentioning
confidence: 99%
“…In many types of cancers including HNSCC, the hippo pathway is abnormally inactivated; thus, YAP/TAZ is highly expressed. 31,32 Previous studies have revealed that aberrant Hippo signaling promotes tumor progression including EMT, chemotherapy resistance, and CSCs generation. 33,34 Inhibition of YAP/TAZ using verteporfin (VP) has been recently shown to suppress proliferation and attenuate EMT and stemness in HNSCC CSCs.…”
Section: Introductionmentioning
confidence: 99%
“…The fitness cost of gene knockout can be assessed from programmed gene editing, an approach that is employed for the unbiased identification of essential genes in other organisms and disease settings (Chai et al, 2020; Kim and Hart, 2021). Our present findings confirmed the power of RNA-guided targeted mutation to define essentiality and relevance of parasite proteins in infection-associated morbidity and malignancy.…”
Section: Discussionmentioning
confidence: 99%